Realisasi Metode MOORA Untuk Menentukkan Kelayakan Bakal Calon Kepala Desa - Deddy Supriadi; Herlan Sutisna; Tuti Alawiyah; Rismatul Fauziah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Villages are part of the existing government order in the region. The presence of leaders who have good qualities will bring progress from the village itself. At this time the village has received serious attention from the central government, this aims to promote local wisdom in each village. However, not infrequently the attention given by the central government to the village is not used as well as possible. Unfinished infrastructure development, village services to the community are not good. This problem certainly gives a bad impression. In this case, based on the case study, it is necessary to select a candidate for the village head. The election or selection aims to get candidates for the village head election. Based on this, this study has the aim of realizing the Moora method to determine the feasibility of prospective village heads. The results of the moora method are then made a prototype of the website-based selection information system for the election of village head candidates. With the implementation of the moora method and the design of a website-based system, it provides an update in the selection of prospective village heads.